Synthesis and In-Vitro Activity of New 1 beta-Methylcarbapenem Derivatives as Antibacterial Agents - Jung, Myung-Ho; Hong, Joon Hee; Cho, Jung-Hyuck; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2008)
The synthesis of a new series of 1 beta-methylcarbapenems having pyrrolidine and piperidine moieties is described. Their in-vitro antibacterial activities against both Gram-positive and Gram-negative bacteria were tested and the effect of substituents on the pyrrolidine ring was investigated. A particular compound III b having an oxime-pyrrolidine moiety showed the most potent antibacterial activity.
Keywords: CARBAPENEM ANTIBIOTICS